DESKRIPSI GANGGUAN DISLEKSIA PADA SISWA SEKOLAH DASAR KECAMATAN SEGEDONG - Toni Elmansyah; Riki Maulana; Nini Nini (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Students who have learning difficulties are different from children who have learning problems. learning difficulties in this study focused on impaired children's ability to distinguish letters and write numbers. One of the learning difficulties experienced by students is dyslexia. The purpose of this study was to determine student learning difficulties (dyslexia) of elementary school students in Segedong District. The method used in this research is descriptive method. The stages of the method in this study were in the form of instrument design, interview data collection, observation and data analysis. Based on the results of the study there were 10 students who had symptoms of dyslexia out of a total of 133 students or 7.5% of students who had dyslexia. Most symptoms